Technology integration advancements in distributed systems and computing - Bessis, Nik, 1967- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"The functionality of distributed computing systems has advanced greatly in recent months, and staying abreast of the latest research within the field is difficult. Technology Integration Advancements in Distributed Systems and Computing offers a vital compendium of research and developments within the field of distributed computing, giving case studies, frameworks, architectures, and best practices for academics and practitioners alike. With authors from around the world and the latest research from experts within the field, this resource acts as both a reference guide and research handbook"--Provided by publisher.